ANALISIS POLA KLASTER DAN ORIENTASI PASAR (STUDI KASUS PADA SENTRA INDUSTRI KRIPIK TEMPE SANAN KOTA MALANG, 2014) - Mukaffis, Zaim (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2015)
The purpose of this study is to analyze cluster patterns and market orientation (Case study in center of keripik tempe industries in sanan Malang 2014). Biographical characteristics are consists of age, gender, religion, owners education level of the owners, labor education, and wealth. Total sample in the research are 38 respondents. For the purpose, this study uses Cluster Analysis to analyze cluster pattern refers to the variable in the Markussen model (1996) and Logistic Regression Model is used in this study to analyze the important factors that distinguish export-oriented industries and domestic-oriented industries. The results of the identification of the proposed cluster patterns Markusen, it can be concluded that the pattern of industrial district of keripik tempe industries in sanan Malang Regency follows the pattern of clusters Marshallian and the Hub and Spoke. The results of binary logistic regression model analysis in this study showed that of seven independent variables, there are two variables that significantly influence the export market orientation of the age of business and the active promotion. While the training, the labor, the buyer network, technology and network suppliers of raw materials has no effect on export market orientationKeywords: Cluster Patterns, Market Orientation, Marshallian, Hub and Spoke